Consuming Eid Al-Adha - Ahmed, Amar (Poligrafi, 2020)
There is a lacuna in ethnographic research with regards to Muslims’ identity construction and expression from an internal perspective. Eid Al-Adha is an Islam-ic holiday which is rich in symbolism, collective rituals, and spiritual and material abundance. The article will interpret the meanings and values that consumers of Eid Al-Adha construct as parts of their identity, mainly being the religious one. It will discuss how the holiday expresses significant Muslim values like collectiv-ism, submission to God, sacrifice, charity, patience, and sacredness. Moreover, it will explain possible differences in consumption reflecting particularism due to national and/or cultural identities. The paper furthers our understanding of what Muslims do and say during their consumption of the Day rather than referring to scriptures or scholars. It contributes to the body of knowledge of Muslim holidays, the meanings associated with them, and how celebrators utilize the symbolism within them to construct their identities.
Keywords: consumer culture theory; cultural consumption; Eid Al-Adha; identity; identity construction; identity expression; Individualnost; Islamic culture; Islamska civilizacija; islamska kultura; izražanje identitete; kurban bajram; Muslimani; Muslims; oblikovanje identitete; potrošna kultura; Potrošnja (ekonomija); Religija